Apoptosis‐inducing factor deficient mice fail to develop hepatic steatosis under high fat high fructose diet or bile duct ligation. (6th August 2020) - Sahu, Parul; Mohan, K. Varsha; Aggarwal, Savera; Arindkar, Shailendra; Mahesh Kumar, Jerald; Kumar Upadhyay, Pramod; Ramakrishna, Gayatri; Nagarajan, Perumal
Abstract : Apoptosis‐inducing factor (AIF) is a mitochondrial flavoprotein involved in redox signalling and programmed cell death. The role of AIF has been well recognized in diabetes and obesity. However, the aspect of AIF deficiency in the development of hepatic steatosis and liver injury is unknown. Therefore, in the current study, Harlequin (Hq mutant) mouse with markedly reduced content of AIF was investigated to explore the role of AIF on the initiation of liver injury. The wild type (WT) developed physiological and pathological features of non‐alcoholic fatty liver disease (NAFLD) that were not seen in the Hq mice with AIF deficiency, when fed on high fat high fructose (HFHF) diet. Following bile duct ligation (BDL), the liver associated pathological changes were less conspicuous in Hq mice as compared to WT mice. The expression of AIF protein and apoptosis was markedly lesser as compared to their respective control in Hq mice on HFHF diet. Furthermore, the genes involved in fatty acid metabolism were also altered in the group of treated Hq mice. In conclusion, Hq mice failed to develop diet induced hepatic steatosis, suggestive of a role of AIF mediated pathway in the initiation and progression of liver inflammation. Thus, partial loss of AIF appears to be hepatoprotective. Significance of the study: AIF deficiency has multiple roles in altered pathology processes and cellular metabolism, thereby compromising the cellular homeostasis. Considering the molecular functions of AIF in other organ pathology little is known about its role in diet induced liver injury. Hence, the aim of the current study was to investigate the role of AIF deficiency in liver injury and diseases with focus on NAFLD. The study will help to deliniate the mechanisms of NAFLD using Harliquin Mice.